On Estimation of P(Y - Abdul Hameed, Bsma; Salman, Abbas N.; Kalaf, Bayda Atiya (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The estimation of the stressÙ€ strength reliability of Invers Kumaraswamy distribution will be introduced in this paper based on the maximum likelihood, moment and shrinkage methods. The mean squared error has been used to compare among proposed estimators. Also a Monte Carlo simulation study is conducted to investigate the performance of the proposed methods in this paper.